2016
DOI: 10.1177/1076029616658117
|View full text |Cite
|
Sign up to set email alerts
|

Lessons From the EThIGII Trial

Abstract: This study presents sample size considerations derived from the Efficacy of Thromboprophylaxis as an Intervention during Gravidity (EThIGII) trial (ClinicalTrials.gov: NCT00400387) to address the question of low-molecular-weight heparin (LMWH) treatment in women with recurrent pregnancy loss (RPL) depending on the M2/ANXA5 haplotype. To evaluate the possible influence of such treatment on miscarriage rates of trial participants, a post hoc analysis of ANXA5 promoter genotypes in the light of M2/ANXA5 (RPRGL3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…As such, a sensitivity analysis was conducted focusing on consecutive RPL. The pooled data from 12 studies (seven individual studies [3,11,12,[15][16][17]31] and one group study [1,4,28,32,33] with a sample size of 3,410 subjects showed that women with the M2/ANXA5 haplotype (heterozygous or homozygous) had a significantly higher OR of 1.63 (95% CI, 1.01-2.62, P ¼ .045) compared with women with normal haplotype to have consecutive RPLs (Fig. 2).…”
Section: Association Of the M2/anxa5 Haplotype And Female Rpl Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, a sensitivity analysis was conducted focusing on consecutive RPL. The pooled data from 12 studies (seven individual studies [3,11,12,[15][16][17]31] and one group study [1,4,28,32,33] with a sample size of 3,410 subjects showed that women with the M2/ANXA5 haplotype (heterozygous or homozygous) had a significantly higher OR of 1.63 (95% CI, 1.01-2.62, P ¼ .045) compared with women with normal haplotype to have consecutive RPLs (Fig. 2).…”
Section: Association Of the M2/anxa5 Haplotype And Female Rpl Subjectsmentioning
confidence: 99%
“…Among these 14 studies (Table 1), we observed that five studies used the same parous control group (1,4,16,32,33), but women with RPL were recruited at different times across these studies. We grouped these five studies (justifications for grouping are summarized in Supplemental Table 1) with a total of 183 M2/ANXA5 haplotype carriers; 142 out of them experienced RPL (Fig.…”
Section: Characterization Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Male partners with M2/ANXA5 haplotype are also implied to carry similar risk for RPL (Ang et al, 2019). Recent studies have also proposed that low-molecularweight heparin Fishel et al, 2016;Rogenhofer et al, 2017) and micromolar zinc intake (Danisik et al, 2019) could be the precision anticoagulant interventions for M2/ANXA5 haplotype-associated RPL. Therefore, screening for M2/ANXA5 haplotype for patients afflicted by RPL is recommended as a panel of laboratory investigations (Ang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Patient groups were genotyped by using genomic DNA extracted from peripheral blood and employing Sanger sequencing of the relevant amplicon in line with established protocols [4,19]. The accuracy of the genotyping was verified by a random blinded inclusion of 2% repeated measures.…”
Section: Genotyping Of Anxa5 Proximal Promoter Regionmentioning
confidence: 99%